Alternative means for controlling pomegranate postharvest decay - Mincuzzi, Annamaria; Sanzani, Simona M.; Caputo, Marika; D'Ambrosio, Pasquale; Palou, Lluís; Ragni, Marco; Ippolito, Antonio (ISHS, 2022)
Pomegranate (Punica granatum L.) cultivation in southern Italy is gaining increasing interest due to favorable environmental conditions and the beneficial effects on human health. Both, in the field and postharvest product losses, especially in organic fruit production, represent the chief concern for this high-priced chain. Main postharvest pomegranate diseases are caused by latent pathogens that infect pomegranates during blooming stage (Coniella granati, Alternaria spp., Botrytis spp.), and secondarily by wound pathogens (Penicillium spp. and Aspergillus spp.) affecting fruit during processing from harvest until storage.